The influence of teacher support on student engagement in physical education among college students: The mediating effects of autonomous motivation and self-efficacy - Qi Guo; Xiaopeng Wang; Zhendong Gao; Jianxin Gao; Xiaofei Lin; Shamsulariffin Samsudin (PLoS ONE, 2025)
Student engagement is a malleable behavior shaped by instructional environments and widely regarded as a key component of higher education quality. Nevertheless, many college students have inadequate positive experiences with physical education classes, characterized by a lack of engagement. Therefore, framed within the self-determination theory and social cognitive theory, the present empirical research investigates how autonomy, relatedness, and competence support are associated with student engagement during physical education learning, focusing on the mediating variables of autonomous motivation and self-efficacy. Data collection involved a cross-sectional survey administered to undergraduates from four colleges located in Jiangxi Province, China. After excluding invalid questionnaires, 406 eligible responses were included in the data analysis. Structural equation modelling was then constructed through AMOS 26.0 for hypothesis testing. According to the findings, teacher autonomy and relatedness support were significantly related to student engagement, while competence support showed no significant correlation. Additionally, the pathways from autonomy and competence support to student engagement were both mediated by autonomous motivation. However, its mediating role was not supported in the link between relatedness support and student engagement. Furthermore, teacher autonomy, competence, and relatedness support all significantly influence student engagement via self-efficacy. The present study explores the relational mechanisms linking teacher support to student engagement in college physical education. These results contribute to refining teaching strategies to enhance student engagement while providing insights into optimally motivating instruction in higher education physical education teaching.